"That's what you do for people you love": A qualitative study of social support and recovery from a musculoskeletal injury. - Khic-Houy Prang; Sharon Newnam; Janneke Berecki-Gisolf (PLoS ONE, 2018)
Social support has been identified as a significant factor in facilitating better health outcomes following injury. However, research has primarily focused on the role of social support from the perspective of the person experiencing an injury. Limited research has examined the experiences of the family members and friends of a person with injury. This study aims to explore the perceptions and experiences of social support and recovery following a transport-related musculoskeletal injury (MSI) in a population of injured persons and their family members and friends.This study was conducted using a phenomenological qualitative research design. In-depth semi-structured interviews were conducted with ten persons with MSI, recruited via the Transport Accident Commission (TAC) in Victoria, Australia. Seven family members and friends were also interviewed. The data was analysed using constant comparative method and thematic analysis.Several themes were identified including: (1) key sources and types of support received, (2) relationship development and (3) challenges of providing and receiving support. Participants with MSI reported stories about how the social network provided emotional and tangible support. Family members and friends confirmed the supportive acts provided to the participants with MSI. Positive iterative changes in relationships were reported by the participants with MSI. Participants with MSI, their family members and friends described several difficulties including loss of independence, feeling like a burden, and the impact of caring on health and well-being.The role of social support is complex given the multitude of people involved in the recovery process. The findings of this study suggest that persons with MSI may benefit from support groups and maintenance of existing support networks. Furthermore, family members and friends engaged in the recovery process may benefit from support in this role.